An Approach of SMEs Financial Performances from An European Perspective - Delia Buceag (CES Working Papers, 2010)
SMEs form one of the sectors mostly affected by this financial crisis, due to their lack of financial power. Still, a HVI analysis indicates this period as favorable to any SME that manages to identify and to react promptly to market changes. Most of the times, managers tend to focus on the technical and practical aspects of the manufacturing process, underestimating the financial management and the real facts related to the operations under their control. Starting from these thoughts, the hereby article approaches the real need for specific training in the field of financial reports and indicators aiming to draw the attention to the performances that may be achieved by the small and medium size enterprises, performances that mainly depend on the effective financial management, on the good understanding of basic accounting notions and on an adequate decision making process. Even after 20 years of ,,capitalism” and democracy, the Romanian SMEs are still at a low level. This is not discouraging, although, having in view the lack of liquidities at global level, the possibility to get a bank loan is limited, and the over-exigency of commercial banks. Thus, the long-term loans designed for SME's and corporations become more and more difficult to get . Despite these, performances can still be achieved, even on the background of a deep crisis. Compared to the big companies from EU and not only, the advantage of SME's is their increased flexibility and their capacity to implement new services and to market new products. In the absence of higher levels of decision and approval, the decision-making process in SME's is easier and thus, more efficient. In this context, SME's may act promptly by applying solutions adjusted to the market conditions. (Ciobanu, 1998, p. 98 ) ”The small entrepreneurs are the engine of the economy” is a well-known saying, but we are still far from reaching the level of the European Union.
Keywords: 330; financial performance; medium and small enterprises; European Union; new perspectives